Principles of corporate finance - Brealey, Richard A. (New York: McGraw Hill, 2023)
"This book describes the theory and practice of corporate finance. We hardly need to explain why financial managers have to master the practical aspects of their job, but we should spell out why down-to-earth managers need to bother with theory. Managers learn from experience how to cope with routine problems. But the best managers are also able to respond to change. To do so you need more than time honored rules of thumb; you must understand why companies and financial markets behave the way they do. In other words, you need a theory of finance"--
Includes bibliographical references and index.
Keywords: Corporations -- Finance